Balance Analysis of Microstrip-to-CPS Baluns and Its Effects on Broadband Antenna Performance - Dong Sik Woo; Young-Ki Cho; Kang Wook Kim (International Journal of Antennas and Propagation)
Amplitude and phase balances of two types of microstrip-(MS-) to-coplanar stripline (CPS) baluns have been analyzed through simulations and measurements, and their effects on broadband antenna performance are investigated. The impedance bandwidth of the balun determined by a back-to-back configuration can sometimes overestimate the balun operating bandwidth. With the conventional balun with a 180° phase delay line, it is observed that the balun balance over the operating frequencies becomes much more improved as the CPS length increases to over 0.1 λg. As compared with the conventional balun, the proposed MS-to-CPS balun demonstrated very wideband performance from 5 to over 20 GHz. With the proposed balun, amplitude and phase imbalances are within 1 dB and ±5°, respectively. Effects of the balun imbalance on overall broadband antenna performance are also discussed with a quasi-Yagi antenna and a narrow beamwidth tapered slot antenna (TSA).